2008
DOI: 10.1007/s10722-008-9380-4
|View full text |Cite
|
Sign up to set email alerts
|

Agro-morphological diversity of Spanish traditional melons (Cucumis melo L.) of the Madrid provenance

Abstract: The variability of 14 landraces belonging to a Madrilean village historically specialized on melon cultivation, Villaconejos, was evaluated based on 58 quantitative and qualitative morphological traits. These landraces were compared to a reference array composed of 14 accessions which represented the main varieties cultivated in Spanish fields. Individual data related to plant, fruit, seed and phenology have been analysed using a multivariate analysis. This analysis showed intra-and inter-varietal diversity, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
25
0
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 5 publications
4
25
0
1
Order By: Relevance
“…The lack of consistency observed in the clustering of accessions from the same botanical group in this study is similar to the results of Escribano and Lázaro (2009), and it is associated with the quantitative nature of characteristics because of environmental influence. Moreover, morphological descriptors divided 29 accessions of melon including inodorus, flexuosus, and dudaim varieties into eight groups without an association with the taxonomic type (Soltani et al, 2010).…”
supporting
confidence: 82%
See 3 more Smart Citations
“…The lack of consistency observed in the clustering of accessions from the same botanical group in this study is similar to the results of Escribano and Lázaro (2009), and it is associated with the quantitative nature of characteristics because of environmental influence. Moreover, morphological descriptors divided 29 accessions of melon including inodorus, flexuosus, and dudaim varieties into eight groups without an association with the taxonomic type (Soltani et al, 2010).…”
supporting
confidence: 82%
“…Therefore, the characterization of the accessions based on descriptors of the fruit (Table 1) showed great variability, even within the same botanical group, which is consistent with reports of polymorphisms of Cucumis melo (Staub et al, 2004;Nakata et al, 2005;Escribano and Lázaro, 2009). It is noteworthy that these morphological methods, which are the basis for traditional systematics, are irreplaceable in the evaluation of genetic resources and are necessary for initial assessment of diversity and precise identification of traditional cultivars (Konopka and Hanson, 1985).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…As stated by Escribano and Lázaro (2009), morphological analyses are an absolute requirement for the initial evaluation of genetic resources and the accurate identification of local landraces. Several studies have morphologically characterized local germplasms and found them to represent different genetic sources (Decker-Walters et al, 2002;Liu et al, 2004;Staub et al, 2004;Laghetti et al, 2008;Escribano and Lázaro, 2009;Szamosi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%